(untitled) (The Pakistan Development Review, 2006)
“Issues in Pakistan’s Economy” by S. Akbar Zaidi was first published in 1999. The book provided comprehensive information on different aspects of the economy in Pakistan since independence. The idea of writing this book originated from Oxford University Press as there was no book on the economy of Pakistan to benefit the graduate students, researchers, scholars, academicians, and the general public. The book was prescribed as a standard text book in the area of issues in Pakistan’s economy. It is also used as a standard book on the courses on South Asia’s development, economic history, and political economy of the region. The book became a best seller due to its subject matter. That is why a great need was felt to update the book that forced the author to expand, update, and revise the book and improve the shortcomings left in the previous edition. The Second edition includes a large amount of new research material. Also, the most recent available data have been included in the tables of the text throughout the book. Three new chapters have been added, some of the chapters have been reformulated, and the new arrivals in theory and empirical research have also been incorporated, accordingly. The book under review presents the important issues in the form of boxed text, appendices, chapter summaries, and provides suggested readings to further enhance the knowledge in specific areas. The efforts and the pains of the author in completing this book are highly laudable in producing such a valuable piece of research on economic development in Pakistan over the fifty-seven years to benefit the end users in completing their studies, research work, and policy-oriented assignments.